2021
DOI: 10.3390/jpm11111214
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Virtual Reality Devices on Pain and Anxiety in Patients Undergoing Cystoscopy Performed under Local Anaesthesia

Abstract: Background: Bladder cancer is one of the most common malignancies. Its diagnosis is based on transurethral cystoscopy. Virtual reality (VR) is a three-dimensional world generated through the projection of images, the emission of sounds and other stimuli. VR has been proven to be a very effective “distractor” and, thus, a useful tool in managing pain. The aim of this study was to determine whether the use of VR sets is technically feasible during the cystoscopy and whether the use of VR devices would reduce the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Ten of the 13 studies demonstrated a favorable effect on pain with the use of VR compared with standard intraprocedural care (77% (95% CI: 38%-100%), P = 0.046). 5,16,17,29,41,42,46,47,55,56 The overall median effect size was −0.33 (95% CI: −0.76 to 0.08) (I 2 = 66%) for the VR group compared with the control. The direction of effect and median effect sizes within the “incision” (−0.39 [95% CI: −0.98 to 0.20] [I 2 = 46%]) and “endoscopic” (−0.33 [95% CI: −0.72 to 0.06] [I 2 = 73%]) subgroups were similar, indicating a lack of subgroup difference.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Ten of the 13 studies demonstrated a favorable effect on pain with the use of VR compared with standard intraprocedural care (77% (95% CI: 38%-100%), P = 0.046). 5,16,17,29,41,42,46,47,55,56 The overall median effect size was −0.33 (95% CI: −0.76 to 0.08) (I 2 = 66%) for the VR group compared with the control. The direction of effect and median effect sizes within the “incision” (−0.39 [95% CI: −0.98 to 0.20] [I 2 = 46%]) and “endoscopic” (−0.33 [95% CI: −0.72 to 0.06] [I 2 = 73%]) subgroups were similar, indicating a lack of subgroup difference.…”
Section: Resultsmentioning
confidence: 99%
“…5,81 Thirteen trials displayed relaxing, nature-related content on the VR headsets. 1,5,11,17,41,42,46,47,55,56,72,78,81 Two studies included only female patients, 1,17 whereas 1 study included only male patients. 83 No significant differences in age were noted between the VR and control groups.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations